Gambaran Karakteristik Demografi Dan Perkembangan Pada Anak Usia 2-5 Tahun di Puskesmas Kesesi I - Luthfia Kalfikasari; Neti Mustikawati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The development of children under five is an increasingly complex body structure and function that occurs in a regular and predictable pattern as a maturation process. Children's development can be assessed from their speech and language abilities, fine or gross motor skills, cognitive intelligence, and social or emotional abilities. This study aims to describe the demographic and developmental characteristics of stunted children aged 2-5 years at the Kesesi I health center. This research is a descriptive study. This sampling technique used total sampling, the population of this study was 38 children at the Kesesi I Community Health Center. This research instrument used the Pre-Developmental Screening Questionnaire (KPSP) which was recommended by the Ministry of Health of the Republic of Indonesia for use in this study, so validity and reliability tests were not carried out. . The data analysis used was univariate in the form of a percentage frequency distribution. The results of this study show that the average child at the Kesesi I Community Health Center is 42 months old. Male gender (71.1%), spontaneous birth (81.6%), term gestation (37-42 weeks) (81.6%), weight at birth with sufficient birth weight (2500-4000 grams) (89.5%), current BB in the normal category (68.4%), current TB in the normal category (60.5%) and (100%) children have a history of breastfeeding. The development of toddlers at the Kesesi I Community Health Center shows that (55%) of respondents have doubtful development. The conclusion obtained is that 55% of the demographic and developmental characteristics of stunted children aged 2-5 years at the Kesesi I Community Health Center have doubtful development.